THE EFFECT ON PARAOXONASE AND ARYLESTERASE ACTIVITIES OF PROPOLIS AGAINST CHROMIUM IN CYPRINUS CARPIO - Yonar, M. Enis; Yonar, Serpil Mise; Coban, M. Zulfu; Eroglu, Mucahit (Parlar Scientific Publications (P S P), 2012)
The aim of the present study was to investigate the protective effect of propolis against the toxic effects of chromium (VI) by examining paraoxonase (PUN) and arylesterase (ARE) enzyme activities in Cyprinus carpio. The fish (100 +/- 5 g) were exposed to sublethal concentrations of chromium (15, 30, and 60 mu g/L). Propolis (5 mg and 10 mg propolis per kg fish weight) was simultaneously administered to chromium-exposed fish. Treatment was continued for 28 days, and at the end of this period, blood samples were collected. PUN and ARE enzyme activities were determined in serum. Reductions in PUN and ARE enzyme activities were observed in chromium exposed fish. Simultaneous treatment with propolis significantly increased serum PUN and ARE enzyme activities.
Keywords: Fish; Cyprinus carpio; chromium; propolis; paraoxonase; arylesterase